Effects of Road and Bridge Infrastructure Development on the Local Economy in Tabalong Regency - Andrianto, Agus; Udiansyah, Udiansyah; Yunani, Ahmad (Pancasila International Journal of Applied Social Science, 2024)
Infrastructure development, particularly in the form of roads and bridges, plays a pivotal role in driving economic advancement and improving societal well-being in Tabalong Regency. This study aims to comprehensively evaluate the economic impacts of road and bridge infrastructure investments in Tabalong Regency. Utilizing secondary data sourced from the Tabalong Regency Statistics Office (BPS), the research employs a quantitative approach, primarily through regression analysis, to examine the relationship between infrastructure investments and economic indicators. The findings reveal significant positive correlations between infrastructure development and various economic metrics. Enhanced road and bridge networks are shown to facilitate smoother transportation of goods and people, reduce logistical costs, and improve market accessibility for businesses. This, in turn, stimulates economic activities, boosts productivity, and attracts investments into the region. Moreover, improved infrastructure supports the development of other sectors such as tourism, agriculture, and manufacturing, creating a multiplier effect on economic growth. Based on the research outcomes, it is recommended that Tabalong Regency continues to prioritize and invest in infrastructure projects, particularly those related to roads and bridges. Sustained investments in infrastructure not only support current economic activities but also lay the groundwork for future development opportunities.